Isolation and Characterization of Clinical Listeria monocytogenes in Beijing, China, 2014–2016 - Zhang, Xiaoai; Niu, Yanlin; Liu, Yuzhu; Lu, Zheng; Wang, Di; Cui, Xia; Chen, Qian; Ma, Xiaochen (Frontiers in Microbiology, 2019)
Listeria monocytogenes is an important foodborne pathogen with a significant impact on public health worldwide. A great number ofMany outbreaks caused by L. monocytogenes hasve been reported, especially in the United States and European countries. However, listeriosis has isuncommonnot yet been included ina notifiable disease in China, and thus information on this infection has been scarce among the Chinese population.there is no fewreports of human outbreaks so far. In this study, we described a three-year surveillance of listeriosis in Beijing, China. Fifty-six L. monocytogenes strains isolated from 49 clinical infectious cases (27 pregnancy-associated infections, 22 non-pregnancy-associated infections)between 2014 and 2016 in Beijing were analyzed by serotyping, pulsed field gel electrophoresis (PFGE), multi-locus sequence typing (MLST) and antimicrobial susceptibility testing between 2014 and 2016 in Beijing. The predominant serotypeserogroups were 1/2a,3a and 1/2b,3b,7 which accountinged for 92% of the overall isolates. Four strains were erotypeserogroup 4b,4d,4e, isolated from patients with pregnancy-associated infections. Based on PFGE, these isolates were divided these isolates into 27 32 pulsotypes (PTs) and 3 clusters associated with serotypeserogroups. TwelveTen PTs were represented by more than one isolate with PT09 containing the most number of isolates. MLST differentiated the isolates into 18 STs, with noout new ST designated. The three most common STs were ST8 (18.4%), ST5 (16.3%), ST87 (12.2%), accounting for 46.9% of the isolates. STs prevalent in other parts of the world were also present in China such as ST1, ST2, ST5, ST8, and ST9 which caused maternal fetal infections or outbreaks. However, the STs and serotypeserogroup distribution of clinical L. monocytogenes in Beijing, China was different with that of strainsfrom those in other countries. High congruence between MLST and pregnancy-associated infectionswas found. Strains of ST1 and ST2 were isolated from patients with pregnancy-associated infection, whereas none of ST155 isolates caused pregnancy-associated cases. Surveillance of molecular characterization will provide important information for prevention of listeriosis. This study also enhances our understanding of genetic diversity of clinical L. monocytogenes in China.